PROVENANCE OF PINDOS FLYSCH DEPOSITS IN METSOVO AND FOURNA AREAS USING SCANNING ELECTRON MICROSCOPY AND MICROANALYSIS - Ananiadis, G.; Vakalas, I.; Zelilidis, A.; Tsikouras, B. (Bulletin of the Geological Society of Greece, 2004)
Pétrographie observation of sandstones that contain detrital grains and lithic fragments along with microanalytical data from certain minerals suggest that detrital material in Pindos flysch deposits, in Metsovo and Fourna areas, may have been sourced in the Pindos ophiolite and the Pelagonian metamorphic rocks; additionally some material from Fournas has probably been derived from the Koziakas ophiolite outcrop. The Loumnitsa Unit (Pindos ophiolite), has probably supplied the Pindos foreland with ma+erial from the erosion of amphibolites while the Dramala Unit was the most probable source of spinels and ultramafic material. Fragments of acid plutonio rocks have been observed, too, owing their origin from the plutonite of Vamounta-Kastoria (Pelagonian Zone). The area of Fourna has been also fed by the Koziakas ophiolites, as evidenced from the composition of chlorites and epidotes.